Progestin as an alternative treatment option for multi-treated recurrent triple-negative breast cancer (Swiss Medical Weekly, 2013)
OBJECTIVE: Patients with recurrent triple-negative breast cancer (TNBC) currently have no established treatment option other than chemotherapy. However, long-term chemotherapy is often difficult due to adverse effects. A previous study documented a 10%–30% response rate of progestins in oestrogen receptor–negative breast cancer. The aim of this study was to investigate the effect of medroxyprogesterone/megestrol acetate (MPA/MA) in patients with recurrent TNBC. METHODS: This retrospective observational analysis included 51 patients with recurrent TNBC; 17 were treated with MPA/MA and 34 underwent chemotherapy. The two groups were matched at a 1:2 ratio according to age, metastatic sites, and salvage treatment lines. Efficacy was compared using the χ2 and rank-sum tests. Progression-free survival (PFS) was calculated using the Kaplan–Meier method, and the two groups were compared using the log-rank test. RESULTS: The two groups were well balanced in terms of age, disease-free survival, number of metastases, and salvage therapy lines. Clinical benefit rates in the MPA/MA and chemotherapy groups were 52.94% and 73.53%, respectively (χ2 test, p = 0.208), and median PFS was comparable between groups (log-rank test, p = 0.135). Median PFS of 1st–6th-line salvage treatments was shorter in the MPA/MA group than in the chemotherapy group (log-rank test, p = 0.036), but median PFS of ≥7th-line salvage treatments was comparable (log-rank test, p = 0.139). Eight patients discontinued chemotherapy due to adverse effects, and one patient withdrew from MPA treatment because of weight gain. CONCLUSIONS: Progestins (MPA/MA) are an alternative treatment option for multi-treated recurrent TNBC.